Developing ASEAN‐5 bond markets: what needs to be done?. (May 2014) - Gray, Simon; Felman, Joshua; Carvajal, Ana; Jobst, Andreas A.
<x xml:space="preserve">Abstract</x> This paper examines development challenges facing bond markets in the ASEAN‐5 (Indonesia, Malaysia, Philippines, Singapore, and Thailand). It first assesses their level of development, finding that bond market frameworks—that is, the quality of the physical infrastructure, monitoring, and regulation—compare favourably with those in other emerging markets. The paper then considers possible further enhancements, including changes in disclosure practices as well as reforms of ratings agencies, central bank liquidity management, and taxation. It also considers steps to develop derivatives markets, which in some countries remain quite small. Finally, the article draws lessons from the global financial crisis in developed markets for the future development of ASEAN‐5 markets.